Fungsi Kesenian Dikia Rabano dalam Prosesi Arak-arakan Mempelai pada Upacara Pesta Perkawinan di Minangkabau - Syeilendra Syeilendra (International Conference on Languages and Arts, 2012)
Dikia Rabano as one of traditional arts of Minangkabau, is still used dominantly by the society in a ritual parade of bride and bridegroom of wedding celebration. The function of Dikia Rabano is as (1) entertainment and performance for the society that watch it, (2) a musical communication tool, and (3) emotional expression of the performants and their audience.